2019
DOI: 10.3892/ol.2019.10968
|View full text |Cite
|
Sign up to set email alerts
|

Propofol exhibits a tumor‑suppressive effect and regulates cell viability, migration and invasion in bladder carcinoma by targeting the microRNA‑10b/HOXD10 signaling pathway

Abstract: 2,6-diisopropylphenol (propofol) is a commonly used intravenous anesthetic drug, which has been reported to serve an antitumor role in human cancers. The current study aimed to assess the effects of propofol on the biological behaviors of human bladder cancer cells and to elucidate its potential molecular mechanism. The results of MTT, wound healing and Matrigel invasion assays demonstrated that propofol significantly inhibited the viability, migration and invasion of bladder cancer T24 cells in vitro. Reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Garib et al (25) reported that propofol increased the migration of breast cancer cells; however, Miao et al (26) suggested that propofol inhibited the invasion of colon cancer cells. Qi et al (27) revealed a tumor-suppressive effect of propofol in BC by suppressing cell proliferation, migration and invasion. In the present study, it was revealed that propofol inhibited the viability, migration and invasion of BC cells in vitro, and suppressed tumor xenograft growth in vivo; this was consistent with previous reports that propofol exhibits antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…Garib et al (25) reported that propofol increased the migration of breast cancer cells; however, Miao et al (26) suggested that propofol inhibited the invasion of colon cancer cells. Qi et al (27) revealed a tumor-suppressive effect of propofol in BC by suppressing cell proliferation, migration and invasion. In the present study, it was revealed that propofol inhibited the viability, migration and invasion of BC cells in vitro, and suppressed tumor xenograft growth in vivo; this was consistent with previous reports that propofol exhibits antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…20 In addition, propofol plays an antitumor role through regulating the viability, migration and invasion of bladder cancer by targeting the microRNA-10b/HOXD10 signaling pathway. 21 On the other hand, studies have confirmed that midazolam and Rop synergistically inhibit bone cancer pain in rats with different mechanisms. 22 Moreover, Rop also plays an important role in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to anesthesia, propofol also affects immunity, inflammation, and ischemia reperfusion injury 4 , 19 . Propofol has been reported to induce antitumor immunity by promoting T-assisted cell activation and differentiation 20 22 and can inhibit the viability, migration, and invasion of bladder cancer T24 cells in vitro 23 . In this study, we explored the effects of propofol on the proliferation, migration, and stem-like properties in three bladder cancer cell lines, identified its underlying mechanisms, and further validated its effects in primary human bladder cancer cells and mice xenografts in vivo .…”
Section: Discussionmentioning
confidence: 99%